High voltage low cobalt ternary cathode material, its manufacturing method and its use

The high voltage low cobalt ternary cathode material addresses the issue of poor cycle stability and safety in high-nickel materials by controlling lithium-nickel mixing and reducing cobalt content, achieving enhanced capacity, energy density, and stability at high voltages.

JP2025512035AInactive Publication Date: 2025-04-16WANHUA CHEM GRP CO LTD
View PDF 14 Cites 0 Cited by

Patent Information

Application Number
JP2024560336
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2022-12-09
Filing Date
2023-07-25
Publication Date
2025-04-16
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing high-nickel ternary cathode materials for lithium-ion batteries suffer from poor cycle stability and safety due to cracking and powdering caused by excessive delithiation, leading to irreversible phase changes and volume shrinkage.

Method used

A high voltage low cobalt ternary cathode material with the general formula Li_{a}Ni_{b}Co_{c}Mn_{d}O_{2} is developed, where the lithium-nickel mixing ratio is controlled between 2 and 7, and the cobalt content is reduced while manganese content is increased, adjusting the electron energy level structure to maintain structural integrity and stability at high voltages.

Benefits of technology

The material achieves higher capacity and energy density at high voltages while maintaining excellent cycle stability and safety, reducing volume changes and preventing cracking and powdering, thus extending the material's life and improving safety.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025512035000001
    Figure 2025512035000001
  • Figure 2025512035000002
    Figure 2025512035000002
  • Figure 2025512035000003
    Figure 2025512035000003
Patent Text Reader

Abstract

The present invention provides a high voltage, low cobalt ternary cathode material having the general formula Li a Ni b Co c Mn d O 2 (wherein 0.97≦a≦1.1, 0.5≦b≦0.76, 0≦c≦0.1, 0.24≦d≦0.5, b+c+d=1, and c<0.35d). Compared with the prior art, the cathode material can be used at a higher voltage than other ternary cathode materials with the same nickel content, increasing the energy density, and the volume change is smaller, which avoids the cracking and powdering of the cathode material, extends the service life of the material, and improves the safety of the material. In addition, the cathode material has a relatively low nickel and cobalt content and a relatively high manganese content, which provides better cycle characteristics and high voltage properties, and reduces the cost of use.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to the field of cathode materials for lithium-ion batteries, and in particular to high voltage low cobalt ternary cathode materials, their methods of manufacture, and their uses. [Background technology]

[0002] Lithium-ion batteries are currently the mainstream energy storage medium around the world and have been increasingly widely used since their invention in the 1990s. At present, whether for motive or non-motive lithium-ion batteries, nickel-cobalt-manganese ternary cathode materials occupy an important position in the market of cathode materials due to their good cycle properties, high capacity and high voltage.

[0003] In the nickel-cobalt-manganese ternary cathode material, it has been generally considered that the role of nickel is to increase the capacity of the material, but when the nickel content is high, that is, in the case of high-nickel ternary cathode materials, lithium and nickel will mix, resulting in lithium precipitation. The role of cobalt is to stabilize the layer structure of the material, reduce the lithium-nickel mixing ratio, and improve the stability of the material during long-term cycles. The role of manganese is to reduce material costs and improve the safety and structural stability of the material.

[0004] In order to further increase the energy density of batteries and extend the driving range of electric vehicles, major power battery manufacturers are gradually promoting development in two directions: higher capacity and higher voltage.

[0005] One of the main ways to achieve high capacity is to increase the nickel content of the ternary cathode material. Generally, a ratio of the molar amount of nickel to the molar amount of lithium higher than 0.8 is considered to be a high-nickel material, but currently there is a trend toward ultra-high nickel (greater than 0.9). However, more and more attention is being paid to the cycle performance and safety of batteries using high-nickel materials.

[0006] The most important reason affecting the cycle performance of high-nickel ternary cathode materials is that they crack and break into powder. Many scientists have conducted in-depth research into the reasons for the powdering of high-nickel ternary cathode materials, and the current consensus in the industry is that, although high-nickel materials have higher capacity than low-nickel materials under the commonly used cut-off voltage of 4.3V, excessive delithiation causes irreversible phase change and leads to more severe volume shrinkage, resulting in cracks within and between primary particles. As the cycles continue, the cracks gradually grow larger and are corroded by the electrolyte, accompanied by the release of active oxygen, which leads to the consumption of the electrolyte, oxidation of the electrolyte, the continuous formation of a new cathode solid electrolyte layer (CEI) and the generation of gas (ACS Energy Lett., 2017, 2, 1150; J. Electrochem. Soc., 2019, 166, A429; ACS Appl. Mater. Interfaces, 2020, 12, 10240), resulting in poor cycle performance and poor safety.

[0007] Among the high voltage ternary cathode materials, currently available materials include NCM523, NCM622, etc., all of which have a cobalt content higher than 0.1. Unlike lithium iron phosphate, the capacity of ternary cathode materials is positively correlated with the cutoff voltage. For example, NCM523 material can only provide a capacity of 162mAh / g when the cutoff voltage is 4.2V, but its capacity can reach 175mAh / g when the voltage is increased to 4.4V. This positive correlation between capacity and voltage is determined by the electronic energy level structure of the three elements nickel, cobalt, and manganese in the ternary cathode material. Simply put, the higher the charging voltage applied to the cathode material, the more low-energy d-orbital electrons on nickel and cobalt can be released and transferred to the negative electrode through the external circuit. Also, more lithium ions are released from the cathode material and transferred to the negative electrode through the electrolyte. However, as the voltage increases, more lithium ions are released, which also causes problems similar to those of high-nickel materials, such as volume shrinkage and collapse of the crystalline layer structure. Furthermore, the material may crack or powder, resulting in failure and deterioration of the cycle characteristics.

[0008] In ternary cathode materials, cobalt has been considered to be very important for the cycling stability of the material. For example, it has been observed that as the Co content increases, the cycling stability of lithium nickel oxide becomes better and better, according to J. Electrochem. Soc., 1999, 146, 3571. Due to the high price of cobalt, both the scientific and industrial communities have attempted to reduce the cobalt content as much as possible, or even to zero, to develop cobalt-free materials. However, it is still commonly recognized in the industry that cobalt plays an essential role in maintaining the stability of the material during long-term cycling, as seen in ACS Energy Lett., 2020, 5, 1814-1824; CN113764653A, and more importantly, under high pressure conditions. To solve the cycle stability of low-cobalt and even cobalt-free materials, the structural or interfacial stability of the material can be improved by optimizing the selection of coating agents (CN111276691A, CN114808127A, CN114853088A, CN114843472A, etc.), doping with multiple elements (CN112993239A, CN114759183A, CN114709378A, etc.), or using other elements such as Al / W / Ti / Mg / Fe instead of Co (CN113800574A, CN111816877A, etc.). However, all of these methods require the introduction of new elements, making the process more complicated, and the small amount of other elements doped does not solve the fundamental problem of the collapse of the layered structure caused by excessive delithiation due to voltage increase, so the deterioration of cycle stability caused by the lack of cobalt cannot be completely solved. Recently, Tesla's chief scientist Jeff Dahn said that Li[Ni 0.5 Mn 0.3 Co 0.2In the article "O2 as a Superior Alternative to LiFePO4 for Long-Lived Low Voltage Li-Ion Cells," we proposed a new solution that we believe can improve the cycling stability of ternary cathode materials. This solution uses a battery core made of NCM523 cathode material that cycles only at 3.65V or 3.8V or less, and the battery core can be cycled for more than 100 years at 20°C. However, in this solution, the charge / discharge voltage is too low, so the NCM523 material can only provide a capacity of less than 110mAh / g at 3.8V, which does not contribute to improving the energy density.

[0009] In the use of ternary cathode materials, the intermixing of lithium and nickel has been considered detrimental to cycling (Nat. Comm. 2014, 5, 3529; Chem. Mater. 2007, 19, 1790). Recently published patents such as CN113584590A, CN113809320A, CN113707874A, and CN104409700A all believe that certain measures, such as doping with different elements or special steps such as gradual replenishment sintering of lithium, are required to reduce the degree of intermixing of lithium and nickel in the cathode material.

[0010] Therefore, how to maintain the high energy density of ternary cathode materials while reducing the cobalt content to reduce costs and maintain high cycling stability is a challenging issue. Summary of the Invention [Problem to be solved by the invention]

[0011] The present inventors have found that, unlike conventional knowledge, in the ternary cathode material, by controlling the nickel content, reducing the cobalt content, and increasing the manganese content to a certain extent, the electronic energy level structure of the low-cobalt ternary cathode material is adjusted to increase its operating voltage, limiting the amount of lithium ions released at high voltage, and preventing the structure from collapsing due to excessive delithiation, the low-cobalt cathode material can exert higher capacity at high voltage to obtain high energy, while maintaining excellent cycle stability. Furthermore, by controlling the mixture of lithium and nickel to a certain extent (lower is not better), the nickel in the lithium layer can play a role in maintaining the integrity and stability of the layered structure under high voltage cycle conditions. Compared with the cobalt-rich cathode material with the same nickel content, the low-cobalt cathode material has further improved cycle stability at high voltage.

[0012] Therefore, in response to the shortcomings of the prior art, the present invention aims to provide a high voltage low cobalt ternary cathode material with superior cycle characteristics and high voltage properties compared to other ternary cathode materials with the same nickel content. [Means for solving the problem]

[0013] In order to achieve the above object of the present invention, the present invention provides a compound represented by the general formula Li a Ni b Co c Mn d A high voltage low cobalt ternary cathode material having O2 (where 0.97≦a≦1.1, 0.5≦b≦0.76, 0≦c≦0.1, 0.24≦d≦0.5, b+c+d=1, and c<0.35d) is provided.

[0014] According to the cathode material of the present invention, said cathode material has a lithium nickel loading (σ) of 2≦σ≦7. The lithium nickel loading is defined as the molar percentage of the lithium content in the nickel layer relative to the total lithium content.

[0015] According to the cathode material of the present invention, in terms of capacity, in an operating voltage range of 3 to 4.3V, the cathode material has a 0.1C capacity of 185mAh / g or less, and in an operating voltage range of 3 to 4.5V, the 0.1C capacity is 210mAh / g or less.

[0016] According to the cathode material of the present invention, the cathode material is used at an operating voltage of 4.3V or more, preferably at an operating voltage of 4.35V or more, and more preferably at an operating voltage of 4.40V or more.

[0017] According to the cathode material of the present invention, the cathode material has a lower cobalt content and a higher manganese content than the conventionally used ternary cathode material with the same nickel content, the cobalt content is less than 0.35 times the manganese content, and the lithium-nickel mixing ratio is 2-7. On the other hand, when the nickel, cobalt and manganese contents in the cathode material are within the above ranges, the d-orbital electron energy of the nickel and cobalt elements is moved to a lower energy level, and a larger difference occurs between the p energy level of the cathode material and lithium, so that the charge and discharge voltage is increased. The energy density is increased by increasing the charge and discharge voltage of the cathode material. The applicable charge and discharge voltage of the cathode material can reach up to 4.5V. At a charge and discharge voltage of 4.5V or less, the volume change of the cathode material is smaller, so that cracking and powdering inside and between the primary particles are prevented, the service life of the cathode material is extended, and the safety of the material is improved. On the other hand, when the nickel, cobalt and manganese contents of the cathode material are within the above ranges, the low-cobalt ternary cathode material has a limited number of lithium ions that can be desorbed at a given voltage compared to a cobalt-rich ternary cathode material having the same nickel content but a nickel content of more than 0.1, thereby enabling the low-cobalt ternary cathode material to exhibit a suitable high capacity and preventing deterioration of cycle characteristics caused by the collapse of the layered structure of the cathode material due to excessive delithiation.

[0018] Another object of the present invention is to Step 1: dissolving NiSO4·6H2O, MnSO4·H2O, and CoSO4·7H2O in deionized water to obtain a salt solution; Add deionized water to the reaction vessel, add concentrated ammonia water to the deionized water to prepare a base solution containing ammonia water, and simultaneously add the salt solution obtained in step 1, sodium hydroxide solution, and concentrated ammonia water to the base solution. An overflow port is provided in the reaction vessel, and as the salt solution, sodium hydroxide solution, and concentrated ammonia water are dropped, the particle size D in the reaction vessel is increased. 50 Step 2 overflows continuously until it reaches the target granularity. Step 3: removing all the slurry from the reaction vessel, subjecting it to solid-liquid separation, washing with deionized water, and baking to obtain a nickel cobalt manganese hydroxide precursor; Step 4: homogeneously mixing the nickel cobalt manganese hydroxide precursor with LiOH·H2O or lithium carbonate; and step 5, sintering the mixture obtained in step 4 under oxygen atmosphere to obtain a low-cobalt ternary cathode material.

[0019] According to the production method of the present invention, in step 2, the dropping rate of the salt solution is controlled to 300 mL / h to 500 mL / h, for example, 300 mL / h, 350 mL / h, 400 mL / h, 450 mL / h, 500 mL / h, the dropping rate of the concentrated ammonia water is controlled to 6 mL / h to 10 mL / h, for example, 6 mL / h, 7 mL / h, 8 mL / h, 9 mL / h, 10 mL / h, and the dropping rate of the sodium hydroxide solution is controlled so that the pH of the entire reaction solution is 10.00 to 13.00, for example, 10.00, 10.50, 11.00, 11.50, 12.00, 12.50, 13.00.

[0020] According to the production method of the present invention, the ammonia water-containing base solution used in step 2 is a base solution containing 0.1 to 0.8 M ammonia water, preferably a base solution containing 0.3 to 0.5 M ammonia water, the concentrated ammonia water used in step 2 is an ammonia water solution having a concentration of 20% to 28%, preferably an ammonia water solution having a concentration of 25%, and the sodium hydroxide solution used in step 2 is a sodium hydroxide solution having a concentration of 30% to 42%, for example, a sodium hydroxide solution having a concentration of 30% to 32%, or a sodium hydroxide solution having a concentration of 40% to 42%, preferably a sodium hydroxide solution having a concentration of 32%.

[0021] According to the manufacturing method of the present invention, the particle size D obtained in step 2 50 The target particle size is 3 to 20 μm, preferably 5 to 15 μm.

[0022] According to the production method of the present invention, in step 4, the molar ratio of the nickel cobalt manganese hydroxide precursor to LiOH·H2O or lithium carbonate is 1:1.01 to 1:1.10, preferably 1:1.02 to 1:1.05, for example, 1:1.02, 1:1.03, 1:1.04, 1:1.05.

[0023] According to the manufacturing method of the present invention, in step 5, the sintering temperature is 700°C to 1000°C, for example, 700°C, 750°C, 800°C, 820°C, 850°C, 890°C, 900°C, 920°C, 940°C, 970°C, or 1000°C, and the sintering time is 10 hours to 14 hours, preferably 11 hours to 13 hours.

[0024] According to the manufacturing method of the present invention, in step 4, a doping process is performed which includes adding one or more compounds containing Ca, Mg, Zr, Sr, Na, Si, Al, La, W, B, Fe, Cu, K, Ge, Nd, Nb, Mo, Y or Ce elements.

[0025] According to the manufacturing method of the present invention, after step 5, a coating treatment is performed which includes adding one or more of compounds containing Ca, Mg, Zr, Sr, Na, Si, Al, La, W, B, Fe, Cu, K, Ge, Nd, Nb, Mo, Y or Ce elements and further sintering the mixture.

[0026] The doping and / or coating process allows the cathode material to better maintain its layered structure during cycling, provide better solvation for lithium ions, or improve the electronic and ionic conductivity of the cathode material, thereby more targetedly improving its properties such as cycleability, high temperature resistance, low temperature resistance, rate capability, storage capability, etc.

[0027] The above methods disclosed in the present invention are only intended to illustrate the methods used to achieve the low cobalt ternary cathode material described in the present invention, and the low cobalt ternary cathode material described in the present invention should not be considered limited by the steps and parameters in the above methods.

[0028] A further object of the present invention is to provide the use of the above high voltage low cobalt ternary cathode material in the manufacture of a positive electrode of a lithium ion battery. Effect of the Invention

[0029] Technical effects The high voltage low cobalt ternary cathode material according to the present invention has the general formula Li a Ni b Co c Mn dO2 (wherein 0.97≦a≦1.1, 0.5≦b≦0.76, 0≦c≦0.1, 0.24≦d≦0.5, b+c+d=1, and c<0.35d), and has a lithium-nickel mixing ratio (σ) of 2≦σ≦7. Compared with the prior art, the cathode material can be used at a higher voltage than other ternary cathode materials with the same nickel content, and has a higher energy density, and has a smaller volume change, which avoids the cracking and powdering of the cathode material, extends the service life of the material, and improves the safety of the material. In addition, the cathode material has a relatively low content of nickel and cobalt and a relatively high content of manganese, which provides better cycle characteristics and high voltage properties, and reduces the cost of use. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0030] The present invention will be further described below with reference to examples, but the present invention is not limited to these examples.

[0031] The main raw material information is as follows: Nickel sulfate hexahydrate NiSO4·6H2O, 262.85g / mol, battery grade, Jinchuan Group Cobalt sulfate heptahydrate CoSO4·7H2O, 281.15g / mol, battery grade, Huayou Cobalt Industry Co., Ltd. Manganese sulfate monohydrate MnSO4·H2O, 169.016g / mol, battery grade, Guizhou Dalong Huicheng New Materials Co., Ltd. Nickel Cobalt Manganese Hydroxide Precursor Ni b Co c Mn d (OH)2, self-made Lithium hydroxide monohydrate LiOH·H2O, 41.96g / mol, Shandong Ruifu Refinery Co., Ltd. Lithium carbonate Li2CO3, 73.89g / mol, Shandong Ruifu Lithium Industry Co., Ltd. Polyvinylidene fluoride (PVDF), analytically pure, Aladdin N-Methylpyrrolidone (NMP), analytically pure, Aladdin Ammonia water (20%-28%), analytically pure, Aladdin Sodium hydroxide solution (32%), analytically pure, Aladdin

[0032] The main test equipment information is as follows: XRD: Malvern Panalytical Aeris X-ray diffractometer Electrochemical test equipment: Shenzhen Xinwei button battery test system Roasting equipment: Hefei Kejing tube furnace, model OTF-1500X

[0033] The lithium-nickel mixing ratio test method is as follows. The cathode material powder was pressed under back pressure and powder XRD measurements were performed using a Malvern Panalytical Aeris XRD tester. The test angle 2θ was 10° to 80°, the step size was 2θ = 0.0108°, and the test time per step was 100 s. The XRD spectra obtained from the test were refined using HighScore software, the refinement steps being as follows: 1. Run the default operation, automatically fit twice, and perform background correction. 2.Load the CIF card and select the 96-400-2444 card. 3. Convert the cards into phases and perform two rounds of auto-refinement. 4. Enter manual refinement mode and refine the background parameters, peak variables, preferred orientation, asymmetry type, and spectral variables in turn. 5. Change the atomic temperature coefficients, where Li is set to 0.0527, Ni / Co / Mn to 0.01232, and O to 0.031663. 6. According to the element contents of the examples, the atomic occupancy values ​​are assigned. First, the initial lithium nickel mixing ratio σ is set to 5, that is, the lithium nickel mixing ratio is defined as the percentage of lithium content in the nickel layer relative to the total lithium content of 5%, for example, LiNi 0.52 Co 0.10 Mn 0.38For O2, Li1 is 0.95, Li2 is 0.05 (i.e., the lithium-nickel mixing ratio σ), Ni1 is 0.47, Ni2 is 0.05, Co is 0.1, Mn is 0.38, and O is 2. 7. Changing the atomic occupancy constraint relationship. LiNi in Example 1 0.52 Co 0.10 Mn 0.38 Taking O2 as an example, we set the constraint relations Li1+Ni2=1, Li2+Li1=1, Ni1+Li2=0.52, and then check the Li1 / Li2 / Ni1 / Ni2 occupancy ratios and perform manual refinement. The refinement is continued until the Weighted R Profile (Rwp) and Rexpected (Rp) values ​​are both lower than 10 (lower values ​​indicate closer between the actual measured spectrum and the simulated spectrum) and the Goodness of Fit (GOF) is less than 1.5, at which point the lithium-nickel mixing ratio σ of this material can be read in the software interface.

[0034] The test method for the electrochemical properties is as follows. A button battery was assembled using the cathode material and lithium sheet obtained in the examples as the positive electrode active material and the negative electrode active material, respectively. The composition of the positive electrode slurry in the positive electrode sheet is the positive electrode active material, acetylene black (conductive agent), and PVDF (binder), with a mass ratio of the three being 80:12:8. For the test, a Shenzhen Xinwei button battery test system is used, and the charge / discharge voltage is set to a set voltage range such as 3.0 to 4.5 V, and the electrochemical characteristics of the button battery assembled with the cathode material are measured in a room temperature environment. The mass specific capacity of the cathode material at a current density of 0.02 A / g (0.1 C) is tested, and then the cycle characteristics of 100 cycles are tested at a current density of 0.2 A / g (1 C), and the cycle retention rate is calculated.

[0035] The DSC test method is as follows: Disassemble the fully charged battery, peel off the cathode material soaked in the electrolyte from the positive electrode sheet, place it in a DSC test device (TOPEM TMDSC), and heat it up to 800°C at a heating rate of 10°C / min to obtain a temperature-heating curve and record the heat generation temperature according to the position of the peak.

[0036] The test method for particle size D50 is as follows. Raw powder is sampled and tested using a Malvern Mastersizer3000 laser particle size analyzer with a wet injector to obtain particle size distribution data. EXAMPLES

[0037] Example 1 2.73 kg of NiSO4·6H2O, 1.284 kg of MnSO4·H2O, and 562 g of CoSO4·7H2O were weighed and dissolved in 6 L of deionized water, and the salt solution was then made up to a volume of 10 L. A 32% sodium hydroxide solution and a 25% aqueous ammonia solution were prepared for use. 9L deionized water was added to a 10L reaction kettle, and about 200mL of concentrated ammonia water was added to the water to prepare a base solution containing 0.3M ammonia water. The salt solution, 32% sodium hydroxide solution, and 25% aqueous ammonia solution were simultaneously dripped into the reaction kettle by a peristaltic pump, and the drip rate of the salt solution was controlled to 400mL / h, the drip rate of the aqueous ammonia was controlled to 8mL / h, and the drip rate of the sodium hydroxide was controlled by an online pH meter, so that the pH of the entire reaction solution was 11.50. An overflow port was provided in the reaction kettle, and as the solution dripped, it overflowed continuously until the particle size D50 of the particles in the reaction kettle was 10μm. Next, all the slurry in the reaction kettle was taken out, separated into solid and liquid by a centrifuge, and washed with deionized water. After washing, the wet solid was transferred to an oven and baked at 120℃ for 10 hours, and Ni 0.52 Co 0.10 Mn 0.38 2885 g of (OH) was obtained. Ni 0.52 Co 0.10 Mn 0.38Mix 100g of (OH)2 and 40.9g of lithium carbonate in a molar ratio of 1:1.03 uniformly using a high-speed mixer. The mixture is placed in a sagger and then placed in a tube furnace and sintered in a pure oxygen atmosphere at 920°C for 12 hours to obtain the cathode material LiNi 0.52 Co 0.10 Mn 0.38 The electrochemical specific capacity and cycle properties of this cathode material were then tested, and the data are shown in Table 1.

[0038] Example 2 3.15 kg of NiSO4·6H2O, 1,014 g of MnSO4·H2O, and 562 g of CoSO4·7H2O were weighed and dissolved in 6 L of deionized water, and the salt solution was then made up to a volume of 10 L. A 32% sodium hydroxide solution and a 25% aqueous ammonia solution were prepared for use. The same method as in Example 1 was used to prepare Ni 0.6 Co 0.1 Mn 0.3 860g of (OH)2 was synthesized. Ni 0.6 Co 0.1 Mn 0.3 Mix 100g of (OH)2 and 40.9g of lithium carbonate in a molar ratio of 1:1.03 uniformly using a high-speed mixer. The mixture is placed in a sagger and then placed in a tube furnace and sintered in a pure oxygen atmosphere at 890°C for 12 hours to obtain the cathode material LiNi 0.6 Co 0.1 Mn 0.3 The electrochemical specific capacity and cycle properties of this cathode material were then tested, and the data are shown in Table 1.

[0039] Example 3 3.15 kg of NiSO4·6H2O and 1,352 g of MnSO4·H2O were weighed out and dissolved in 6 L of deionized water, and the salt solution was then adjusted to a constant volume of 10 L. 32% sodium hydroxide solution and 25% ammonia water solution were prepared for use. The same method as in Example 1 was used to prepare Ni 0.6 Mn 0.4 855g of (OH)2 was synthesized. Ni0.6 Mn 0.4 Mix 100g of (OH)2 and 40.9g of lithium carbonate in a molar ratio of 1:1.03 uniformly using a high-speed mixer. The mixture is placed in a sagger and then placed in a tube furnace and sintered in a pure oxygen atmosphere at 890°C for 12 hours to obtain the cathode material LiNi 0.6 Mn 0.4 The electrochemical specific capacity and cycle properties of this cathode material were then tested, and the data are shown in Table 1.

[0040] Example 4 3.668 kg of NiSO4·6H2O, 845 g of MnSO4·H2O, and 281 g of CoSO4·7H2O were weighed and dissolved in 6 L of deionized water, and the salt solution was then made up to a volume of 10 L. A 32% sodium hydroxide solution and a 25% aqueous ammonia solution were prepared for use. The same method as in Example 1 was used to prepare Ni 0.70 Co 0.05 Mn 0.25 872g of (OH)2 was synthesized. Ni 0.70 Co 0.05 Mn 0.25 Mix 100g of (OH)2 and 46.80g of LiOH·H2O in a molar ratio of 1:1.03 uniformly using a high-speed mixer. The mixture is placed in a sagger and then placed in a tube furnace and sintered in a pure oxygen atmosphere at 820℃ for 12 hours to obtain the cathode material LiNi 0.70 Co 0.05 Mn 0.25 The electrochemical specific capacity and cycle properties of this cathode material were then tested, and the data are shown in Table 1.

[0041] Example 5 3.15 kg of NiSO4·6H2O, 1,014 g of MnSO4·H2O, and 562 g of CoSO4·7H2O were weighed and dissolved in 6 L of deionized water, and the salt solution was then made up to a volume of 10 L. A 32% sodium hydroxide solution and a 25% aqueous ammonia solution were prepared for use. The same method as in Example 1 was used to prepare Ni 0.6 Co 0.1 Mn0.3 860g of (OH)2 was synthesized. Ni 0.6 Co 0.1 Mn 0.3 100g of (OH)2 and 40.9g of lithium carbonate were mixed uniformly in a molar ratio of 1:1.03 in a high-speed mixer, and then 0.1g of alumina and 0.3g of zirconia were added to the high-speed mixer and mixed uniformly. The mixture was then placed in a sagger, which was then placed in a tube furnace and sintered in a pure oxygen atmosphere at 890°C for 12 hours to obtain a cathode material LiNi doped with trace amounts of aluminum and zirconium. 0.6 Co 0.1 Mn 0.3 The electrochemical specific capacity and cycle properties of this cathode material were then tested, and the data are shown in Table 1.

[0042] Example 6 3.15 kg of NiSO4·6H2O, 1,014 g of MnSO4·H2O, and 562 g of CoSO4·7H2O were weighed and dissolved in 6 L of deionized water, and the salt solution was then made up to a volume of 10 L. A 32% sodium hydroxide solution and a 25% aqueous ammonia solution were prepared for use. The same method as in Example 1 was used to prepare Ni 0.6 Co 0.1 Mn 0.3 860g of (OH)2 was synthesized. Ni 0.6 Co 0.1 Mn 0.3 Mix 100g of (OH)2 and 40.9g of lithium carbonate in a molar ratio of 1:1.03 uniformly using a high-speed mixer. The mixture is placed in a sagger and then placed in a tube furnace and sintered in a pure oxygen atmosphere at 890°C for 12 hours to obtain the cathode material LiNi 0.6 Co 0.1 Mn 0.3 102g of O2 was obtained. 100 g of this cathode material was mixed uniformly with 0.3 g of alumina in a high-speed mixer, the mixture was placed in a sagger, and then placed in a tube furnace and sintered for 12 hours at 400°C in a pure oxygen atmosphere to obtain a cathode material LiNi 0.6 Co0.1 Mn 0.3 100 g of O2 was obtained. The electrochemical specific capacity and cycle properties of this cathode material were then tested, and the data are shown in Table 1.

[0043] Comparative Example 1 2.625 kg of NiSO4·6H2O, 1.014 kg of MnSO4·H2O, and 1.124 kg of CoSO4·7H2O were weighed and dissolved in 6 L of deionized water, and the salt solution was then made up to a volume of 10 L. A 32% sodium hydroxide solution and a 25% aqueous ammonia solution were prepared for use. The same method as in Example 1 was used to prepare Ni 0.5 Co 0.2 Mn 0.3 880g of (OH)2 was synthesized. Ni 0.5 Co 0.2 Mn 0.3 100g of (OH)2 and 40.9g of lithium carbonate were mixed uniformly in a molar ratio of 1:1.03 using a high-speed mixer. The mixture was placed in a sagger and then placed in a tube furnace and sintered in an oxygen atmosphere at a temperature of 920°C for 12 hours to obtain the cathode material LiNi 0.5 Co 0.2 Mn 0.3 The electrochemical specific capacity and cycle properties of this cathode material were then tested, and the data are shown in Table 1.

[0044] Comparative Example 2 3.15 kg of NiSO4·6H2O, 676 g of MnSO4·H2O, and 1124 g of CoSO4·7H2O were weighed out and dissolved in 6 L of deionized water, and the salt solution was then adjusted to a constant volume of 10 L. 32% sodium hydroxide solution and 25% ammonia water solution were prepared for use. The same method as in Example 1 was used to prepare Ni 0.6 Co 0.2 Mn 0.2 866g of (OH)2 was synthesized. Ni 0.6 Co 0.2 Mn 0.2Mix 100g of (OH)2 and 40.9g of lithium carbonate in a molar ratio of 1:1.03 uniformly using a high-speed mixer. The mixture is placed in a sagger and then placed in a tube furnace and sintered in a pure oxygen atmosphere at 890°C for 12 hours to obtain the cathode material LiNi 0.6 Co 0.2 Mn 0.2 100 g of O2 was obtained. The electrochemical specific capacity and cycle properties of this cathode material were then tested, and the data are shown in Table 1.

[0045] Comparative Example 3 3.15 kg of NiSO4·6H2O and 1,352 g of MnSO4·H2O were weighed and dissolved in 6 L of deionized water, and the salt solution was then adjusted to a constant volume of 10 L. 32% sodium hydroxide solution and 25% ammonia water solution were prepared for use. The same method as in Example 1 was used to prepare Ni 0.6 Mn 0.4 891g of (OH)2 was synthesized. Ni 0.6 Mn 0.4 Mix 100g of (OH)2 and 40.9g of lithium carbonate in a molar ratio of 1:1.03 uniformly using a high-speed mixer. The mixture is placed in a sagger and then placed in a tube furnace and sintered in a pure oxygen atmosphere at 940°C for 12 hours to obtain the cathode material LiNi 0.6 Mn 0.4 The electrochemical specific capacity and cycle properties of this cathode material were then tested, and the data are shown in Table 1.

[0046] Comparative Example 4 3.93 kg of NiSO4·6H2O, 507 g of MnSO4·H2O, and 562 g of CoSO4·7H2O were weighed and dissolved in 6 L of deionized water, and the salt solution was then made up to a volume of 10 L. A 32% sodium hydroxide solution and a 25% aqueous ammonia solution were prepared for use. The same method as in Example 1 was used to prepare Ni 0.75 Co 0.1 Mn 0.15 876g of (OH)2 was synthesized. Ni 0.75 Co 0.1 Mn0.15 Mix 100g of (OH)2 and 46.80g of LiOH·H2O in a high-speed mixer with a lithiation ratio of 1:1.03. Put the mixture into a sagger and place it in a tube furnace. Sinter it in a pure oxygen atmosphere at 820℃ for 12 hours to obtain the cathode material LiNi 0.75 Co 0.1 Mn 0.15 The electrochemical specific capacity and cycle properties of this cathode material were then tested, and the data are shown in Table 1.

[0047] Comparative Example 5 4.2 kg of NiSO4·6H2O, 338 g of MnSO4·H2O, and 562 g of CoSO4·7H2O were weighed and dissolved in 6 L of deionized water, and the salt solution was adjusted to a constant volume of 10 L. 32% sodium hydroxide solution and 25% ammonia water solution were prepared for use. Ni with a particle size of 10 μm was prepared by the same method as in Example 1. 0.8 Co 0.1 Mn 0.1 894g of (OH)2 was synthesized. Ni 0.8 Co 0.1 Mn 0.1 Mix 100g of (OH)2 and 46.80g of LiOH·H2O in a molar ratio of 1:1.03 uniformly using a high-speed mixer. The mixture is then placed in a sagger and placed in a tube furnace, where it is sintered in a pure oxygen atmosphere at 800℃ for 12 hours to obtain the cathode material LiNi 0.8 Co 0.1 Mn 0.1 The electrochemical specific capacity and cycle properties of this cathode material were then tested, and the data are shown in Table 1.

[0048] Comparative Example 6 4.2 kg of NiSO4·6H2O, 507 g of MnSO4·H2O, and 281 g of CoSO4·7H2O were weighed and dissolved in 6 L of deionized water, and the salt solution was then made up to a volume of 10 L. A 32% sodium hydroxide solution and a 25% aqueous ammonia solution were prepared for use. The same method as in Example 1 was used to prepare Ni 0.8 Co 0.05 Mn 0.15857g of (OH)2 was synthesized. Ni 0.8 Co 0.05 Mn 0.15 Mix 100g of (OH)2 and 46.80g of LiOH·H2O in a molar ratio of 1:1.03 uniformly using a high-speed mixer. The mixture is then placed in a sagger and placed in a tube furnace, where it is sintered in a pure oxygen atmosphere at 800℃ for 12 hours to obtain the cathode material LiNi 0.8 Co 0.05 Mn 0.15 The electrochemical specific capacity and cycle properties of this cathode material were then tested, and the data are shown in Table 1.

[0049] Comparative Example 7 2.1 kg of NiSO4·6H2O, 1.521 kg of MnSO4·H2O, and 843 g of CoSO4·7H2O were weighed and dissolved in 6 L of deionized water, and the solution was then adjusted to a volume of 10 L. A 32% sodium hydroxide solution and a 25% aqueous ammonia solution were prepared for use. The same method as in Example 1 was used to prepare Ni 0.4 Co 0.15 Mn 0.45 823g of (OH)2 was synthesized. Ni 0.4 Co 0.15 Mn 0.45 Mix 100g of (OH)2 and 40.9g of lithium carbonate in a molar ratio of 1:1.03 uniformly using a high-speed mixer. The mixture is placed in a sagger and then placed in a tube furnace and sintered in a pure oxygen atmosphere at 800°C for 12 hours to obtain the cathode material LiNi 0.4 Co 0.15 Mn 0.45 The electrochemical specific capacity and cycle properties of this cathode material were then tested, and the data are shown in Table 1.

[0050] Test example: Electrochemical property test According to the above-mentioned electrochemical property test method, lithium-nickel mixing ratio test method and DSC test method, the relevant tests were carried out, and the test results are shown in Table 1.

[0051] [Table 1]

[0052] As is clear from Table 1, when Example 1 is compared with Comparative Example 1, the lithium-nickel mixing ratio in Comparative Example 1 is too low, and the cycle retention rate is too low, and the DSC heat generation onset temperature is low, which shows that an appropriate lithium-nickel mixing ratio is advantageous for maintaining the stability of the structure.

[0053] Comparing Example 2 and Comparative Example 2, the lithium-nickel mixing ratio in Comparative Example 2 was too low, the cycle retention rate was too low, and the DSC heat generation onset temperature was low, which shows that an appropriate lithium-nickel mixing ratio is advantageous for maintaining the stability of the structure.

[0054] Comparing Example 3 with Comparative Example 3, in Comparative Example 3, the mixed ratio of lithium nickel was too high, the cycle retention rate was too low, and the capacity was too low.

[0055] Comparing Example 4 and Comparative Example 4, the lithium-nickel mixing ratio in Comparative Example 4 was too low, the cycle retention rate was too low, and the DSC heat generation onset temperature was low, which shows that an appropriate lithium-nickel mixing ratio is advantageous for maintaining the stability of the structure.

[0056] In Comparative Examples 5 and 6, the lithium-nickel mixing ratio is within an appropriate range, but the nickel content is too high, the capacity is too high, and the cycle retention rate is low in both cases.

[0057] In Comparative Example 7, the nickel content was too low and the lithium-nickel mixing ratio was too high, so that the heat generation initiation temperature was improved, but the capacity was too low, resulting in a low cycle retention rate.

[0058] As described above, the high voltage low cobalt ternary cathode material according to the present invention has the general formula Li a Ni b Co c Mn dO2 (wherein 0.97≦a≦1.1, 0.5≦b≦0.76, 0≦c≦0.1, 0.24≦d≦0.5, b+c+d=1, and c<0.35d), and a lithium-nickel mixing ratio (σ) of 2≦σ≦7. The high voltage low cobalt ternary cathode material of the present invention can be used at operating voltages of 4.3V or higher, even as high as 4.5V. The cathode material increases the energy density and has a smaller volume change, which avoids cracking and powdering of the cathode material, extends the service life of the material, which shows good capacity retention during cycling, and improves the safety of the material, which shows a higher heat generation temperature in DSC tests. The cathode material also has a relatively low nickel and cobalt content and a relatively high manganese content, which provides better cycle characteristics and high voltage properties, while reducing the cost of use.

Claims

1. General formula Li a Ni b Co c Mn d O 2 where 0.97≦a≦1.1, 0.5≦b≦0.76, 0≦c≦0.1, 0.24≦d≦0.5, b+c+d=1, and c<0.35d.

2. 2. The cathode material of claim 1 having a lithium nickel admixture (σ) of 2≦σ≦7.

3. The cathode material according to claim 1 or 2, which has a capacity of 185 mAh / g or less at 0.1 C in an operating voltage range of 3 to 4.3 V, and 210 mAh / g or less at 0.1 C in an operating voltage range of 3 to 4.5 V.

4. The cathode material according to any one of claims 1 to 3, for use at an operating voltage of 4.3V or more, preferably for use at an operating voltage of 4.35V or more, more preferably for use at an operating voltage of 4.40V or more.

5. NiSO 4 ・6H 2 O, MnSO 4 ・H 2 O, and CoSO 4 ・7H 2 Step 1: dissolving O in deionized water to obtain a salt solution; Add deionized water to a reaction vessel, and then add concentrated ammonia water to the deionized water to prepare a base solution containing ammonia water. The salt solution obtained in step 1, the sodium hydroxide solution, and the concentrated ammonia water are simultaneously added dropwise to the base solution. An overflow port is provided in the reaction vessel, and the particle size D in the reaction vessel is increased as the salt solution, the sodium hydroxide solution, and the concentrated ammonia water are added dropwise. 50 Step 2, which continually overflows until Step 3: removing all the slurry from the reaction vessel, subjecting it to solid-liquid separation, washing with deionized water, and baking to obtain a nickel-cobalt-manganese hydroxide precursor; Nickel cobalt manganese hydroxide precursor and LiOH·H 2 Step 4 of homogeneously mixing the mixture with O or lithium carbonate; and step 5, sintering the mixture obtained in step 4 in an oxygen atmosphere to obtain a low-cobalt ternary cathode material.

6. 6. The method according to claim 5, wherein in step 2, the dripping rate of the salt solution is controlled to 300 mL / h to 500 mL / h, the dripping rate of the concentrated ammonia water is controlled to 6 mL / h to 10 mL / h, and the dripping rate of the sodium hydroxide solution is controlled so that the pH of the entire reaction solution is 10.00 to 13.

00.

7. The method according to claim 5 or 6, wherein the aqueous ammonia-containing base solution used in step 2 is a base solution containing 0.1 to 0.8 M aqueous ammonia, preferably a base solution containing 0.3 to 0.5 M aqueous ammonia, the concentrated aqueous ammonia solution used in step 2 is an aqueous ammonia solution having a concentration of 20% to 28%, preferably an aqueous ammonia solution having a concentration of 25%, and the sodium hydroxide solution used in step 2 is a sodium hydroxide solution having a concentration of 30% to 42%, preferably a sodium hydroxide solution having a concentration of 32%.

8. Particle size D obtained in step 2 50 The method according to any one of claims 5 to 7, wherein the target particle size is 3 to 20 μm.

9. In step 4, nickel cobalt manganese hydroxide precursor and LiOH.H 2 The method according to any one of claims 5 to 8, wherein the molar ratio of O or lithium carbonate is from 1:1.01 to 1:1.10, preferably from 1:1.02 to 1:1.

05.

10. The method according to any one of claims 5 to 9, wherein in step 5, the sintering temperature is 700°C to 1000°C, and the sintering time is 10 hours to 14 hours.

11. The manufacturing method according to any one of claims 5 to 10, wherein in step 4, a doping process is performed, which includes adding one or more of compounds containing Ca, Mg, Zr, Sr, Na, Si, Al, La, W, B, Fe, Cu, K, Ge, Nd, Nb, Mo, Y or Ce elements.

12. 12. The method according to any one of claims 5 to 11, wherein after step 5, a coating treatment is performed which comprises adding one or more of the compounds containing the elements Ca, Mg, Zr, Sr, Na, Si, Al, La, W, B, Fe, Cu, K, Ge, Nd, Nb, Mo, Y or Ce and re-sintering the mixture.

13. Use of the high voltage low cobalt ternary cathode material according to any one of claims 1 to 4 in the manufacture of a positive electrode for a lithium ion battery.

Citation Information

Patent Citations

  • Positive electrode material for lithium-ion battery and preparation method of positive electrode material

    CN105870408A

  • High-nickel low-cobalt type high-voltage-resistant ternary positive electrode material and preparation method thereof

    CN111384392A

  • Single-crystal ternary positive electrode material, preparation method thereof and lithium ion battery

    CN112018372A

  • High-voltage ternary positive electrode material with core-shell structure and preparation method of high-voltage ternary positive electrode material

    CN114361440A

  • Continuous and stable preparation method of ternary precursor for lithium ion battery

    CN114804223A